Impacts of the COVID-19 pandemic on the mental health of older adults - Braun, Isabelle; Gonçalves, Gabriella; Piber, Leonardo; Neves, Lucas; Guimarães, Graziella (Brazilian Journal of Global Health, 2022)
OBJETIVO: A Covid-19 causada pela SARS-CoV-2 teve seu início em Wuhan, na China e em pouco tempo se alastrou pelo mundo tornando-se uma pandemia. Com essa problematização, vários governos adotaram políticas como isolamento social num esforço para reduzir as taxas de infecção, limitando a propagação da doença, principalmente em populações com maior risco como os idosos. Esse trabalho objetivou avaliar o impacto da pandemia na saúde mental dos idosos. MÉTODOS: Realizou-se um estudo observacional analítico transversal quantitativo, cuja população foi de idosos (acima de 65 anos), da cidade de São Paulo - SP, Brasil; por meio de questionário online (Google Forms®) norteado pelo Patient Health Questionnaire-9 (PHQ- 9), Escala de Depressão Geriátrica (EDG), Inventário de Ansiedade Geriátrica (GAI) e pela Escala de Ansiedade de Beck (BAI). Na análise estatística foi utilizado o teste de Mann Whitney, considerando um p<0,05. RESULTADOS: Um total de 208 idosos responderam ao questionário, sendo 33% homens e 67% mulheres, dentre eles 30% moravam sozinhos. Houve associação estatisticamente significativa entre o sexo e sentir-se sozinho (p= 0.015) e considerar que a ajuda profissional, mesmo que virtual, minimizaria os efeitos do isolamento social (p=0.030), evidenciando esta relação com as mulheres. CONCLUSÃO: Conclui-se que a população idosa merece atenção no que se refere aos cuidados em saúde mental durante a pandemia, em função das consequências do isolamento social. Infere-se que os idosos têm senso crítico sobre sua saúde mental e sinalizam a necessidade de auxílio social e clínico. DESCRITORES: Saúde-Mental, Idoso, Pandemia, COVID-19, Isolamento Social. ABSTRACT OBJECTIVE: Covid-19 caused by SARS-CoV-2 began in Wuhan, China and in a short time spread across the world, becoming a pandemic. With this problematization, several governments adopted policies such as social isolation in an effort to reduce infection rates, and limiting the spread of the disease, especially in populations at greater risk, such as older adults. This study aimed to evaluate the impact of the pandemic on the mental health of older adults. METHODS: A quantitative, cross-sectional, analytical observational study was carried out, with a population of older adults (over 65 years old), from the city of São Paulo - SP, Brazil; through an online questionnaire (Google Forms®) guided by the Patient Health Questionnaire-9 (PHQ- 9), Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and the Beck Anxiety Scale (BAI). In the statistical analysis, the Mann Whitney test was used, considering p<0.05. RESULTS: A total of 208 older people answered the questionnaire, 33% men and 67% women, of whom 30% lived alone. There was a statistically significant association between sex and feeling alone (p= 0.015) and in considering that professional help, even if virtual, would minimize the effects of social isolation (p=0.030), with evidence of this relationship among women. CONCLUSION: It is concluded that the older population deserves attention with regard to mental health care during the pandemic, due to the consequences of social isolation. It is inferred that older adults have a critical sense of their own mental health, signaling the need for social and clinical assistance. DESCRIPTORS: Mental Health, Older adults, Pandemic, COVID-19, Social Isolation.